Behavioral intervention to increase honest responses using pledges - Velina Hristova; Kelly A. Schmidtke; Lora Lyubenova; Fadi Makki; Ivo Vlaev (Humanities & Social Sciences Communications)
Abstract Honest reporting is essential for maintaining trust and efficiency in various domains, including volunteer recruitment. However, individuals often misrepresent their qualifications due to social pressures or incentives to appear more suitable. This study investigates whether an honesty pledge can enhance truthful self-reporting in a high-stakes volunteer application process. Using a randomized controlled trial with 12,388 applicants for the FIFA World Cup 2022™ Volunteer Program, we examined whether an honesty pledge influenced self-reported English and Arabic language proficiency. Results indicate that participants who received the honesty pledge were more likely to report higher English proficiency compared to those who did not receive the pledge, suggesting a potential self-justification or aspirational reporting effect rather than a reduction in dishonesty. Conversely, non-Arabic-speaking participants in the pledge group were less likely to inflate their Arabic proficiency, aligning with prior findings that honesty pledges can reduce misreporting in lower-stakes contexts. These findings highlight the context-dependent nature of honesty pledges, particularly in competitive selection processes where mandatory qualifications may heighten impression management. The study contributes to the broader literature on behavioral nudges and honesty interventions, emphasizing the need for a nuanced approach when applying honesty pledges in real-world, high-stakes settings.